Keefektifan Media Real Reading Aided Learning untuk Meningkatkan Keterampilan Membaca Permulaan dengan Berbantuan Lagu pada Siswa Kelas I SD - Heni, Ristiya; Sutikno, Putri Yanuarita (Paedagogie, 2026)
This study aims to analyze the effectiveness of Real Reading Aided Learning (ReAL) media in improving the early reading skills of first grade elementary school students. The study used a quantitative approach with a quasi-experimental design of the pretest-posttest control group type. The research subjects were 55 students divided into a control class (27 students) and an experimental class (28 students). Data collection techniques included observation, documentation, and an early reading ability test that had been tested for validity and reliability. Data analysis was carried out through normality tests, homogeneity tests, paired t-tests, independent t-tests (Welch), and N-gain calculations using SPSS version 27. The results showed that there was a significant increase in early reading ability in the experimental class with an average gain value of 16.29 and an N-gain of 0.331 (medium category), higher than the control class which obtained an average gain of 4.37 and an N-gain of 0.087 (low category). An independent t-test showed a significant difference in improvement (p < 0.001) with a very large effect size (d > 2.5). Thus, ReAL media is effective in improving the beginning reading skills of first-grade elementary school students.